Enhancing Haematococcus pluvialis biomass and γ-aminobutyric acid accumulation by two-step cultivation and salt supplementation. (August 2019) - Ding, Wei; Cui, Jing; Zhao, Yongteng; Han, Benyong; Li, Tao; Zhao, Peng; Xu, Jun-Wei; Yu, Xuya
Graphical abstract: Highlights: Haematococcus pluvialis was used as a biofeedstock for GABA production. A novel strategy was used to increase H. pluvialis biomass and GABA biosynthesis. The expression of two new genes, gad and cam, was examined. Abstract: The primary goal of this study was to assess the roles of chemical factors and bioprocess strategies on a mixotrophic culture of the microalga Haematococcus pluvialis during γ-aminobutyric acid (GABA) production. A two-stage strategy was used to increase the biomass and GABA accumulation of H. pluvialis . In stage I, mixotrophic growth of H. pluvialis in the presence of fulvic acid (FA) produced a high biomass (1.84 g L −1 ) with a GABA content of 25.45 mg g −1 . Furthermore, a maximum GABA content of 38.57 mg g −1 was obtained when cells were cultured with 0.4 g L −1 NaCl under photoautotrophic conditions in stage II, whereas the carbohydrate content of cells sharply decreased from 26.68 to 18.22%. In addition, salt stress upregulated the expression of the gad and cam genes. The results of this study demonstrate an efficient strategy to produce GABA from the microalga H. pluvialis .